5=r(2r+3)

Simple and best practice solution for 5=r(2r+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5=r(2r+3) equation:


Simplifying
5 = r(2r + 3)

Reorder the terms:
5 = r(3 + 2r)
5 = (3 * r + 2r * r)
5 = (3r + 2r2)

Solving
5 = 3r + 2r2

Solving for variable 'r'.

Reorder the terms:
5 + -3r + -2r2 = 3r + -3r + 2r2 + -2r2

Combine like terms: 3r + -3r = 0
5 + -3r + -2r2 = 0 + 2r2 + -2r2
5 + -3r + -2r2 = 2r2 + -2r2

Combine like terms: 2r2 + -2r2 = 0
5 + -3r + -2r2 = 0

Factor a trinomial.
(1 + -1r)(5 + 2r) = 0

Subproblem 1

Set the factor '(1 + -1r)' equal to zero and attempt to solve: Simplifying 1 + -1r = 0 Solving 1 + -1r = 0 Move all terms containing r to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1r = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1r = 0 + -1 -1r = 0 + -1 Combine like terms: 0 + -1 = -1 -1r = -1 Divide each side by '-1'. r = 1 Simplifying r = 1

Subproblem 2

Set the factor '(5 + 2r)' equal to zero and attempt to solve: Simplifying 5 + 2r = 0 Solving 5 + 2r = 0 Move all terms containing r to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2r = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 2r = 0 + -5 2r = 0 + -5 Combine like terms: 0 + -5 = -5 2r = -5 Divide each side by '2'. r = -2.5 Simplifying r = -2.5

Solution

r = {1, -2.5}

See similar equations:

| 4f-5=8-2f | | 4-5=8-2f | | 35x^2-39x-14=0 | | 5x-2x^2=2 | | 5x^2-46+9=0 | | 0.33z+6=9 | | 5y-2=33 | | 6x+5=78765 | | 6x+5=72 | | 4z+5=18 | | (4x-5)2= | | 8v=3v+20 | | x^3-2x^2-5x+10=0 | | 7u-2=9u | | (3x+8)+(3x-2)=180 | | 2-x=11(x-1) | | (697)(10)= | | 17x^2-11x=0 | | 2x^4y^4+x^3y^3-15x^2y^2=0 | | 36x-9=63 | | 6(4y+14)-13(9y)=100 | | x^2+18x+59=0 | | 8.1x+61.68=-11.9x+60.44 | | 6a^4+7a^2-20=0 | | x*x*x*x-30x*x+125=0 | | 7.2x-3.9=3.3 | | a^4+2a^2-24=0 | | 4x*x*x*x=12x*x | | 5(6z-1)-2(z+3)=21(z+1) | | y^4+y^2-42=0 | | -13x+8x= | | -3(t-4)-(t+9)=3 |

Equations solver categories